"Spark and Cultivate": LISTEN and Grassroots Feminist Activism in the Melbourne Music Scene. (28th June 2016) - Strong, Catherine; Morris, Evelyn
Abstract : LISTEN is a Melbourne-based feminist collective focused on improving the position of women in the music industry, in part achieved through improving the documentation of women's contribution to music. This article includes an interview with founder Evelyn Morris and gives an overview of the development and achievements of LISTEN, whilst placing it in the context of feminist activism in Australia. Morris discusses how LISTEN gave form to the dissatisfaction that was being felt by many women in the Melbourne music scene, and quickly became a hub for a variety of feminist activity. She also elaborates on her own perspectives on what feminism entails, and the recent increase in activism in this area.